Farm size limits agriculture's poverty reduction potential in Eastern India even with irrigation-led intensification - Urfels, Anton; Mausch, Kai; Harris, Dave; McDonald, Andrew J.; Kishore, Avinash; Balwinder-Singh, Poonia, S.; Halsema, Gerardo van; Struik, Paul C.; Craufurd, Peter Q.; Foster, Timothy; Singh, Vartika; Krupnik, Timothy J. (Elsevier, 2023)
CONTEXT Millions of people living in the Eastern Gangetic Plains (EGP) of India engage in agriculture to support their livelihoods yet are income poor, and food and climate insecure. To address these challenges, policymakers and development programs invest in irrigation-led agricultural intensification. However, the evidence for agricultural intensification to lift farmers' incomes above the poverty line remains largely anecdotal.